Do active ETFs gain value over their passive counterparts - Pakkala, Jesse Elias Tapani (My University, 2022)
The purpose of this study is to examine if active ETFs can outperform traditional passive ETFs. This research is using a unique data set of five different ETF pairs from different time periods depending on the ETF pair. The ETF pairs are constructed of two different active and passive ETFs which are investing in the same industry. The key motivation for the study is to find out whether active ETF managers have found a way to take advantage of the active investment style combined with the structure of ETF. ETFs have gained much attention since their release in 1993 and their AUM has risen significantly every year after that. Their structure is tax-efficient for investors and they offer a basket of securities as one unit. This method offers an easy diversification to the investors that lower the risk compared to owning a single stock of a company. The variety of ETFs is wide and investment strategies are versatile. Active ETFs were developed in 2008 and investors' interest in them has risen. The market of active ETFs has still been considerably smaller relative to other ETF markets. They are still new to the investors and understating the benefits of using an active investment style and ETF structure is still developed. The empirical part of this thesis generates answers for investors considering active and passive ETFs. Inside the pairs, active ETFs tend to outperform their passive counterpart in risk-adjusted metrics and annualized returns. However, in some pairs, the time periods are relatively short, and the ETFs are investing in a niche market. The ETFs in the pairs are compared to each other also by the significance of the alpha. This study finds that an active ETF can find statistically significant alpha higher than its passive counterpart. This assumes that active ETFs in a specific environment can outperform their passive counterpart and generate excess returns from the market. This thesis provides new evidence of active ETFs and their performance compared to passive ETFs which are investing in the same industry or niche market. Previous academic literature suggests that in its entirety passive ETFs perform better than active ETFs. In this study, the results are not unanimous with earlier studies since results on some occasions are the opposite.
Keywords: pörssinoteeratut rahastot; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance